A history of old Norse poetry and poetics - Ross, Margaret Clunies 1942- (D.S. Brewer, 2005)
This is the first book in English to deal with the twin subjects of Old Norse poetry and the various vernacular treatises on native poetry that were a conspicuous feature of medieval intellectual life in Iceland and the Orkneys from the mid-twelfth to the fourteenth centuries. Its aim is to give a clear description of the rich poetic tradition of early Scandinavia, particularly in Iceland, where it reached its zenith, and to demonstrate the social contexts that favoured poetic composition, from the oral societies of the early Viking Age in Norway and its colonies to the devout compositions of literate Christian clerics in fourteenth-century Iceland. The author analyses the two dominant poetic modes, eddic and skaldic, giving fresh examples of their various styles and subjects; looks at the prose contexts in which most Old Norse poetry has been preserved; and discusses problems of interpretation that arise because of the poetry's mode of transmission. She is concerned throughout to link indigenous theory with practice, beginning with the pre-Christian ideology of poets as favoured by the god ódinn and concluding with the Christian notion that a plain style best conveys the poet's message
The Old Norse poetic corpus -- An indigenous typology of Old Norse poetry, 1: Technical terms; 2: Genres and sub-genres of Skaldic verse -- Circumstances of recording and transmission -- Old Norse poetic aesthetics -- The impact of Christianity on Old Norse poetry -- Poetics and grammatica, 1: The twelfth century; 2: The Edda of Snorri Sturluson; 3: The third and fourth grammatical treatises -- The Icelandic poetic landscape in the thirteenth and fourteenth centuries
Keywords: Geschichte; Old Norse poetry / History and criticism; Poetics / History; Versdichtung; Poetik; Altnordisch; Literatur